Cutaneous verrucous carcinoma: A clinicopathological study of 21 cases with long-term clinical follow-up - Ye, Qian; Hu, Li; Jia, Meng; Deng, Li-Jia; Fang, Sheng (Frontiers in Oncology, 2022)
Background Cutaneous verrucous carcinoma (CVC) is a rare variant of squamous cell carcinoma and sometimes shares similar clinical and histopathologic features with other verrucous lesions. Methods We performed a retrospective study of 21 patients diagnosed with CVC between 2012 and 2022 by reviewing clinical and histopathological data. We also compared the clinicopathological features of patients with CVC, giant condyloma acuminatum (GCA) and pseudoepitheliomatous hyperplasia (PEH). Follow-up data were obtained by reviewing medical records and telephone interviews. Results The average age of patients with CVC was 63.6 years, with a male predominance. The location of the disease is mostly found in the foot, followed by the lower legs. Histologically, CVC is characterized by an exo-endophytic growth pattern with severe keratinization and a blunted rete ridge with pushing margins. Clinical features including exudation and crusting, induration, irregular borders and warty surface, as well as pathological features including growth pattern, koilocytotic cells, depth and morphologic features of acanthosis, severe keratinization, and degree of dermal inflammation were significant in distinguishing cutaneous CVC, GCA, and PEH. Conclusion Identification of the clinicopathologic features is essential to distinguish CVC from its mimics and to make an early diagnosis. Because of the potential for recurrence and metastasis, CVC requires aggressive treatment.